Visual study of liquid flow in a rotor-stator reactor. (29th September 2015) - Li, Yingwen; Wang, Siwen; Sun, Baochang; Arowo, Moses; Zou, Haikui; Chen, Jianfeng; Shao, Lei
Abstract: A rotor-stator reactor (RSR) is a novel multiphase device which can greatly intensify mass transfer and micromixing processes. However, liquid flow in the reactor is still not very clear. In this work, two different liquids, water and water-in-oil (W/O) microemulsion were used to study liquid flow in the RSR. A high-speed camera was employed to obtain continuous and clear images of liquid flow, and the effects of various operating conditions such as the number of rotor-ring/stator-ring layers, the rotation speed and the liquid volumetric flow rate on the average diameter as well as the average velocity of liquid droplets and the average angle of velocity vector were investigated. Correlations were established to predict the average diameter and the average velocity of the liquid droplets, and the predicted values were found to be in agreement with the experimental values with deviations generally within 15%. Highlights: Liquid flow of water and microemulsion in a rotor-stator reactor (RSR) was studied. A high-speed camera was used to obtain continuous and clear images of liquid flow. Diameter of droplets reduced with increasing layers of rotor-ring/stator-ring. Velocity of droplets rose with increasing layers of rotor-ring/stator-ring. Correlations were established to predict the diameter and velocity of droplets.